(untitled) (Malaysian Journal of Learning and Instruction, 2021)
Purpose – Emotional intelligence abilities of university teachers are more likely to establish suitable emotional teaching and learning environments through their teaching practice, thus promoting learning motivation and engagement among students. Despite the emphasis on the importance of teachers’ emotional intelligence abilities in teaching, it continues to be under-acknowledged and underdeveloped. This is evidenced in a few studies reported on the relationship between emotional intelligence and teaching practice particularly in higher education. Guided by the Four-Branch Emotional Intelligence Ability Model, this study aimed to explore the integration of emotional intelligence in teaching practice among university teachers in higher education. Method – A qualitative design of a descriptive case study was applied on 10 university teachers recruited through purposeful sampling. The data gathered from semi-structured interviews conducted with the university teachers was analyzed through five phases of analysis namely; raw categorization of individual interviewees, group categorization of interviewees, raw key points, refined key points and themes. The credibility and trustworthiness of the data were achieved through prolonged engagement, member check, and interrater reliability. Results – Seven themes namely implementation of structured teaching flow, empathetic pedagogical approach, fostering student learning engagement, consideration of students’ emotions, reflection of university teachers’ characteristics, mutual teaching and learning sessions and meaningful learning sessions were generated. Significance – The study demonstrated the importance of developing emotional intelligence abilities among university teachers as these abilities directly influence teaching and learning processes. In fact, these abilities are subconsciously embedded and demonstrated through teaching practice. Thus training on emotional intelligence needs to be developed by including it as one of the competencies required for university teachers.